The effectiveness of online learning tools using ARCS motivation model - Ramli, Khalijah; Ithnin, Hafini Suhana (2024)
Recently, teaching through online approaches become new phenomena. This trend is escalating during Covid-19 when our teaching and learning had been switching to fully online method. However, it still relevant although our country has announced to endemic phase. The significant of online learning are pursue and still applied with several institution. Online learning cannot be successfully implemented if there is no collaboration with our students. There are several factors that influence students to adapt with new way in teaching and learning process. Within this study, the researcher aims to examine the motivation factors that influence the usage of online learning tools. Using ARCS Motivation factors (attention, relevant, confident and satisfaction), this study explores the relationship and the most influence factor between effectiveness of online learning tools. The data will be collected among students’ part 4 who takes entrepreneurship and management courses in UiTM Perak Branch. A set of questionnaires consist of Part A, B and C will be distribute and analyse using SPSS software. Therefore, this study should give positive impact to education field and government to enhance technology usage in teaching and learning process as well as to shed light on the evolving landscape of education in the digital age and its implications for both learners and educator.